Czechs in Croatia at the turn of the century - Agičić, Damir (Balcanica Posnaniensia. Acta et studia, 2001)
The article is devoted to the presence and role of the Czech national minority in Croatia at the turn of the nineteenth and twentieth centuries. The author addresses the insufficient state of research on the history of Czechs in Croatia and emphasizes the lack of comprehensive studies devoted to this subject. The aim of the work is to outline the main directions for further research on Czech settlement and to demonstrate the significance of Czechs in Croatia’s economic, social, and cultural life. The study employs a historical method based on the analysis of sources and literature concerning Czech migration and Croatian-Czech relations. The author demonstrates that the first larger groups of Czechs appeared in Croatian lands as early as the eighteenth century, while the largest migration wave occurred at the end of the nineteenth century. Settlers concentrated mainly in Slavonia, the Bjelovar region, and the territories of the former Military Frontier. The analysis indicates that the Czechs adapted quickly to their new environment, achieving success in agriculture, craftsmanship, and trade. At the same time, their presence occasionally generated social tensions arising from economic competition and cultural differences. The author highlights the differing relations of Czechs with Croats and Serbs and the role of Czech teachers, craftsmen, publishers, and social activists in the modernization of local communities. The conclusions indicate that the Czech minority played a significant role in Croatia’s economic and cultural development and that its history constitutes an important element of the history of relations among the nations of Central Europe.